Maqashid Sharia as the Foundation of Religious Moderation and Resilience in Aceh's Border Communities - Syamsuar, Syamsuar; Hanif, Hanif; Al-Fairusy, Muhajir; Ikhwan, M.; Putri, Nur Kemala; Alfiansyah, Alfiansyah (Hukum Keluarga Islam IAIN LANGSA, 2024)
The implementation of Islamic law in Aceh over the past two decades has not only reflected the enforcement of Sharia but also illustrated the cultural and political dynamics of Acehnese society. As a region rich in customary law traditions and social pluralism, the response of Acehnese communities, particularly in multicultural border areas, to violations of Islamic law and its existence varies widely. Islamic law in Aceh is often interpreted through the lens of political identity and local culture, while the maqashid sharia values, such as the protection of life, property, and security have yet to be fully integrated into daily practices. This study employs an anthropological approach with qualitative methods. Data collection was conducted through participatory observation, in-depth interviews, and narrative analysis of the experiences and perspectives of local communities. The study focuses on how communities construct, understand, and respond to Sharia as part of their social lives. The findings reveal that border communities in Aceh perceive Islamic law not only as a religious rule but also as a political identity symbol to reinforce their social standing, including in rejecting the construction of non-Muslim places of worship. However, the study also highlights a gap in understanding and applying maqashid sharia, attributed to limited socialization and cross-cultural dialogue. Nevertheless, Islamic law remains respected as a crucial element of the social structure, although its interpretation is often situational and contextual.